The use of quantitative proteomics towards biomarker discovery in lung squamous cell carcinoma - Whitsett, Timothy G. (Transl Lung Cancer Res, 2013)
The high mortality rate in advanced lung cancer, due to a preponderance of tumors discovered at advanced stage, demands the discovery and clinical validation of biomarkers for diagnosing early stage disease. Quantitative proteomics technologies are capable of identifying protein biomarkers with diagnostic, prognostic, and predictive value. Recent works have demonstrated the utility in using quantitative proteomics across normal, pre-cancerous, and cancerous lesions towards the discovery of biomarkers for early stage lung cancer, as well as discovering novel mechanisms of lung carcinogenesis.